A arte do Ssegredo : esoterismo, sigilo e dissimulação política nos séculos XV e XVI - Francisco de Paula Souza de Mendonça Júnior (2014)
We will discuss in this work the role of secret communication on the stage of political action between the XV and XVI centuries, dialoguing with the beginning of the XVII century. Having as main documentary corpus the works of Johannes Trithemius and Giambattista della Porta, we will reflect on how their proposals for encrypted communication of esoteric nature contributed to the political landscape of this period, thinking mainly in its relation to dissimulation, common practice in the social associations of that period. What we sustain in this work is that both Trithemius as Della Porta sought to provide a tool to protect both who serves as well who is served, bringing thus a way to deal with the vagaries of Fortune and the unstable moods of princes, secular or ecclesiastics. This tool was the secret communication, whose cyphers were the result of an esoteric perception of both the language and the universe.